2003
DOI: 10.1007/s00125-003-1090-z
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, and not insulin resistance, is the major determinant of serum inflammatory cardiovascular risk markers in pre-menopausal women

Abstract: Aims/Hypothesis. Increased serum inflammatory markers have been found in obesity and insulin-resistant states, and could play a causative role in insulin resistance, atherosclerosis and cardiovascular disease. The polycystic ovary syndrome represents a human model of insulin resistance because both lean and obese polycystic ovary syndrome patients are insulin-resistant compared with non-hyperandrogenic women. We evaluated whether obesity, insulin resistance, or both, are related to the increased concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
77
3
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 49 publications
15
77
3
3
Order By: Relevance
“…Linear regression models, however, revealed that BMI rather than insulin resistance as indicated by HOMA is the dominant parameter determining IL-6 and CRP values in PCOS, which is consistent with a recent report from a cohort of premenopausal women (28). Since the models explain less than 30% of the variability of plasma IL-6 and CRP, additional factors controlling IL-6 and CRP concentrations in PCOS must be assumed, which are, however, distinct from PCOS-associated endocrine factors such as hyperandrogenemia because none of the parameters of hyperandrogenism correlated with IL-6 or CRP.…”
Section: Discussionsupporting
confidence: 90%
“…Linear regression models, however, revealed that BMI rather than insulin resistance as indicated by HOMA is the dominant parameter determining IL-6 and CRP values in PCOS, which is consistent with a recent report from a cohort of premenopausal women (28). Since the models explain less than 30% of the variability of plasma IL-6 and CRP, additional factors controlling IL-6 and CRP concentrations in PCOS must be assumed, which are, however, distinct from PCOS-associated endocrine factors such as hyperandrogenemia because none of the parameters of hyperandrogenism correlated with IL-6 or CRP.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is in good accordance that in the tree restricted to parameters derived from the medical history and clinical examination, BMI was the most important discriminator. Although BMI is well correlated to the degree of insulin resistance in general [47], it is, however, known that insulin resistance is not only observed in obese PCOS women but also occurs in a substantial proportion of lean PCOS patients as reported by us [29] and others [48]. It is therefore of no surprise that the decision tree which used the unrestricted dataset, including more direct parameters and indices of insulin resistance and altered beta cell function, was superior, and did not include BMI.…”
Section: Discussionmentioning
confidence: 84%
“…[23][24][25] In a recent study of the polycystic ovary syndrome, obesity was reported to be the major determinant in driving the production of markers CRP, IL-6, and tumour necrosis factor. 9 Others found that CRP, in addition to BMI, 26 also correlated with the metabolic syndrome as indicated by insulin resistance, obesity, hypertension, impaired glucose tolerance, low HDL-cholesterol and hypertriglyceridaemia. 26 Similarly, the risk of developing type 2 diabetes in lean and overweight women could be explained by the strong correlation between CRP and fasting hyperinsulinaemia, 27 as CRP correlated independently with insulin sensitivity in healthy non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of CRP, IL-6 and TNF-a in healthy women and women with polycystic ovary syndrome, obesity and not insulin resistance was found to be the major determinant of the inflammatory markers. 9 In contrast, in a study of obese women in which CRP was measured before and after 3 months of reduced energy intake, the relation between CRP concentrations and insulin resistance appeared independent of obesity. 10 The medical treatment of obesity, in particular morbid obesity (BMI Z40 kg/m 2 ), is unsatisfactory and has led to the increased use of surgery worldwide.…”
Section: Introductionmentioning
confidence: 90%